Kierkegaards samtidige - romantikeren Valdemar Thisted - Arffmann, Leif (Kirkehistoriske Samlinger, 1992)
In the years from 1850 to 1870, the theologian Valdemar Thisted was widely read by virtue of his fictional output - Breve fra Helvede (1866) as well as a number of novels. This article discusses the novel Præstekald from 1859, written when the author was vicar of Højrup in North Slesvig. Here, fiction is mixed with theological reflections, mainly of the pastoral kind, showing the difficulty of being a country priest unconversant with agricultural matters. A prominent feature of the book is to be found in a series of letters in which the vicar describes his problems to a friend. As a matter of fact, Thisted in real life wrote letters corresponding to those in the novel. They were directed to Sibbern, a well-known Copenhagen philosopher, whom Thisted had come to know while studying in Copenhagen in the years 1833-40. As it has been pointed out elsewhere, Sibbern was like a father to the students of theology, showing them the warm personal interest that they lacked in their own professors. During his time of study, Thisted also became acquainted with Søren Kierkegaard, a fellow-student. In Præstekald, he tells us that he never understood much of Kierkegaard’s writing, but the novel nevertheless testifies to an inspiration from Kierkegaard, mainly in the critical thoughts about the Church. These reflections seem to have been caused by the Kierkegaard-uproar in North Slesvig in the fifties, shortly before Thisted arrived at Højrup. Præstekald is to be read on this background, but it can also be viewed as a note in the debate about Church-State relations in Denmark, a debate which began in Thisted’s time and which, incidentally, has been renewed in the nineteen-nineties.